2023
DOI: 10.1021/acsomega.3c00526
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Dimeric Pyridinium Bromide Analogues Inhibits Cancer Cell Growth by Activating Caspases and Downregulating Bcl-2 Protein

Abstract: Flexible dimeric substituted pyridinium bromides with primary and tertiary amines are prepared by conventional and solvent-free methods. The formation of compounds 2 and 4 is much easier than that of compounds 1 and 3 because of the benzyl carbon which is more electropositive than the primary alkyl carbon. The newly synthesized dimeric pyridinium compounds are optimized using p). The in vitro antiproliferative activity is studied in lung (A549) and breast cancer cell lines (MDA-MB 231). Among the four compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Many researchers have demonstrated that many anticancer drugs induce apoptosis, which plays an important role in cancer drug development 33 . For this reason, we tested the morphological changes of our new compounds against MDA-MB-231 cells with acridine orange (AO) and ethidium bromide (EB) after 24 h. Morphological assessment demonstrates viable cells (control) with normal morphology and pale green nuclei.…”
Section: Biological Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Many researchers have demonstrated that many anticancer drugs induce apoptosis, which plays an important role in cancer drug development 33 . For this reason, we tested the morphological changes of our new compounds against MDA-MB-231 cells with acridine orange (AO) and ethidium bromide (EB) after 24 h. Morphological assessment demonstrates viable cells (control) with normal morphology and pale green nuclei.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Swiss drug design tools were used to predict the bioavailability of compounds ( 1 – 4 ) 33 . Applications of the Swiss ADME web tool has recently contributed greatly to the design and development of anticancer, tubercular, and antimicrobial agents 33 , 40 , 41 .…”
Section: Biological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost 80-90 percent of novel drug molecules are made of derivatives of heterocyclic compounds. [3][4][5][6] Mohamed et al reported on derivatives of pyridone, thiazolidinone and pyrazolone and studied their anticancer properties against A-549 (lung) and MDA-MB-231 (breast) cancer cell lines using MTT assay. They tested the anticancer properties of nitro-, N,N-dimethyl amino-, methoxy-, and methyl-substituted pyridone derivatives.…”
Section: Introductionmentioning
confidence: 99%